Association between life’s essential 8 and male biochemical androgen deficiency: evidence from NHANES 2013–2016 - Huang, Weisheng; Chen, Mutong; Zhang, Haiyu; Zhang, Zhongfu; Yin, Cong; Huang, Meiyang; Shi, Bentao (Frontiers in Endocrinology, 2024)
Purpose To evaluate the association of Life’s Essential 8 (LE8) and its subscales with male biochemical androgen deficiency (MBAD) and total testosterone based on the data from the national health and nutrition examination survey (NHANES) database. Methods Data of males aged 20 years or older from NHANES of 2013–2016 were extracted. LE8 score was calculated based on American Heart Association definitions. Total testosterone (TT) values were measured in NHANES using precise isotope dilution liquid chromatography. MBAD was defined as serum TT of <300 ng/dL. Univariate and multivariable analyses were conducted. Propensity score matching (PSM) and weighted regression after matching were added as sensitivity analyses. The generalized additive model, smooth curve fitting, and the recursive algorithm were used to determine the potential inflection points. Piecewise regression models with log-likelihood ratio test were used to quantify nonlinear effects. Results A total of 3094 participants who were males and aged 20 years or above were included. Out of them, 805 males were diagnosed with MBAD. After adjusting the confounders in the multivariable model, LE8 was independently associated with MBAD (OR 0.96, P < 0.001) and TT (β 2.7, P < 0.001). The association remained robust even after PSM. The non-linear relationship of LE8 behaviors score with MBAD and TT was revealed. Conclusion LE8 was an independent protective factor of MBAD and a feasible approach to promote male endocrine sexual function.